Control of plant cytokinesis by an NPK1-mediated mitogen-activated protein kinase cascade. - Soyano, Takashi (2002)
Cytokinesis is the last essential step in the distribution of genetic information to daughter cells and partition of the cytoplasm. In plant cells, various proteins have been found in the phragmoplast, which corresponds to the cytokinetic apparatus, and in the cell plate, which corresponds to a new cross wall, but our understanding of the functions of these proteins in cytokinesis remains incomplete. Reverse genetic analysis of NPK1 MAPKKK (nucleus- and phragmoplast-localized protein kinase 1 mitogen-activated protein kinase kinase kinase) and investigations of factors that might be functionally related to NPK1 have helped to clarify new aspects of the mechanisms of cytokinesis in plant cells. In this review, we summarize the evidence for the involvement of NPK1 in cytokinesis. We also describe the characteristics of a kinesin-like protein and the homologue of a mitogen-activated protein kinase that we identified recently, and we discuss possible relationships among these proteins in cytokinesis.